Shortages of Medical Doctors in Indonesia, Is It True? - Sutrisno, MD, PhD, OG (REI) (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
All parts of Indonesia need medical doctors, but it is not a simple thing to be solved. The world of medicine in Indonesia faces many internal problems, specifically regarding medical doctor distribution. Where are the medical doctors in Indonesia being resided? Recently many areas in Indonesia experienced a ratio between doctors and population of more than 1 : 1000. Data from the Indonesia Medical Council (KKI) and Indonesia Medical Doctor Association (IDI) in the year 2023 total number of medical doctors are 214,878 doctors, dominated by general physician 165,453 doctors, and followed by doctors specialist Â 49,425. Total dentists are 41,940, and dentist specialists are 5,201. The fundamental problems, according to population ratios, is related to geographical and demographic handicap because Indonesia is an archipelago country with more than 17,000 islands with more than 280 million populations, with many specific problems in access, Â communication, transportation system, socio-economic, cultural, and leadership.